Alternatives to amalgam: Is pretreatment necessary for effective bonding to dentin?. Issue 11 (November 2022) - Sadeghyar, A.; Lettner, S.; Watts, D.C.; Schedle, A.
Abstract: Objective: The aim of this study was to determine whether pretreatment of the dentin surface is beneficial or not by analysis of the bond strengths of four self-adhesive restoratives and four restoration materials where pretreatment of dentin was necessary. Methods: Bovine incisors (n = 160) were ground flat on the labial surfaces to expose dentin using a grinder and silicon carbide (SiC) abrasive papers under running water. Between preparation and bonding procedures, the crowns were stored in Chloramine-T solution at 4 °C. Eight different restorative materials were studied: Activa BioActive (ABA ), Cention Forte (CNF ), Ceram.x Spectra ST (CXS ), Riva self-cure (RSC ), Equia Forte (EQF ), Fuji II LC (FJI ), Ketac Molar (KTM ), Surefil one (SFO ). Four materials required pretreatment of the dental hard tissue before placement, whereas the other four were self-adhesive (no pretreatment). The specimens were mounted vertically in plaster. A preload of 5 N was applied and the subsequent cross-head speed was 0.8 mm/min. Shear bond strengths (MPa) were calculated as the failure load divided by the bonding area. Failure modes were recorded as adhesive, cohesive or pretest. Data were statistically analyzed via ordinal regression for inference and Tukey's method to adjust for multiple comparisons. All computations were done using R version 4.1.2 (R Core Team 2021). Results: Smax (failure stress in MPa) of the combined groups with pretreatment were significantly higher than the self-adhesive materials. The highest frequency of pretest-failure was seen with FJI . Glass-ionomer cements without pretreatment were the only restoratives with pretest failures. Amongst materials without pretreatment, SFO had the highest bond strengths. Significance: The further reduction of the placement steps for materials used as an amalgam alternative, namely the omission of pretreatment of the dentin, results in these self-adhesive materials having lower bond strengths than materials that require pretreatment of the dentin.